Detection of major gene for Gilles de la Tourette syndrome. - Comings, D E (1984)
The families of 250 consecutive, unselected patients with Tourette syndrome (TS) were analyzed. If the parents had either motor or vocal tics, but not both, there was an increased risk of both TS and tics in the offspring. The mode of inheritance of the combined tic-Tourette trait was evaluated in both nuclear families and extended pedigrees. Complex segregation analysis was carried out allowing for possible contributions from both a major autosomal locus and multifactorial inheritance of variation in the background of each genotype. The most likely mode of inheritance was a major semidominant gene, Ts, with low heritability of the multifactorial background variation. This was true regardless of assumptions about the prevalence of the disorder. The hypothesis of strict multifactorial inheritance could not be rejected with nuclear family data alone. However, the hypothesis of no major gene effect was rejected using data on 3 generations for any estimate of lifetime risk less than 12 per 1,000 in the general population. A pure recessive major gene effect was also rejected. With a gene frequency of approximately .5%, the penetrance was estimated to be about 94% in abnormal Ts/Ts homozygotes, 50% in Ts/ts heterozygotes, and less than 0.3% in normal ts/ts homozygotes. More than two of every three cases are heterozygotes, and nearly all other cases are phenocopies or new mutations. This is the first demonstration by segregation analysis of a major gene in a human neuropsychiatric disorder with a frequency approaching 1% of the population.